International Financial Statistics Supplement on Balance of Payments. (International Financial Statistics; Volume *, ;, 1984)
This article discusses different aspects and tables in the seventh Supplement of Balance of Payments Statistics. A balance of payments statement can be broadly described as the record of an economy's international economic transactions, that is, of the goods and services that an economy has received from, and provided to, the rest of the world, and of changes in the economy's claims on and liabilities to the rest of the world. The report highlights that for recent years the global current account figures contain a large discrepancy that implies either that surpluses are under-recorded, or deficits are over-recorded, or some combination of the two. The inconsistencies that give rise to the recorded current account asymmetry stem mainly from deficiencies in the balance of payments statements of individual countries covered in the statistics. The growth in the discrepancy is most noticeable for the category 'other goods, services, and income'. The problem is still to be resolved, and therefore, considerable caution should be exercised when interpreting the statistics for the most recent years.